Parametric study on the thermal performance and optimal design elements of solar air heater enhanced with jet impingement on a corrugated absorber plate - M. Aboghrara, Alsanossi; Alghoul, Mohammad; Baharudin, B. T. HangTuah; Elbreki, Abdelnaser; A. Ammar, Alhadi; Sopian, Kamaruzzaman; Hairuddin, Abdul Aziz (Hindawi, 2018)
Previous works revealed that cross-corrugated absorber plate design and jet impingement on a flat absorber plate resulted in a significant increase in the performance of a solar air heater (SAH). Involving these two designs into one continuous design to improve the SAH performance remains absent in the literature. This study aimed to evaluate the achieved enhancement on performance parameters of a SAH with jet impingement on a corrugated absorber plate. An energy balance model was developed to compare the performance parameters of the proposed SAH with the other two SAHs. At a clear sky day and a mass flow rate of 0.04 kg/s, the hourly results revealed that the max fluid outlet temperatures for the proposed SAH, jet-to-flat plate SAH, and cross-corrugated plate SAH are 321, 317, and 313 K, respectively; the max absorber plate temperatures are 323.5, 326.5, and 328 K, respectively; the maximum temperature differences between the absorber plate and fluid outlet are ~3, 9, and 15 K, respectively; the max efficiencies are 65.7, 64.8, and 60%, respectively. Statistical t -test results confirmed significant differences between the mean efficiency of the proposed SAH and SAH with jet-to-flat plate. Hence, the proposed design is considered superior in improving the performance parameters of SAH compared to other designs.